Clinical features and potential relevant factors of renal involvement in primary Sjögren's syndrome. (8th November 2018) - Luo, Jing; Xu, Shihao; Lv, Yinqiu; Huang, Xinshi; Zhang, Huxiang; Zhu, Xiaochun; Wang, Xiaobing
Abstract: Objective: To investigate distinct features of renal involvement in patients with primary Sjögren's syndrome (pSS) and to identify potential factors associated with renal involvement. Methods: Four hundred and thrity‐four pSS patients from the Rheumatology Department of the First Affiliated Hospital of Wenzhou Medical University from 2013 to 2017 were included in a cross‐sectional study. Patients with renal involvement were compared with their age‐ and gender‐matched controls (pSS without renal involvement). Demographic, clinical, histological, nephritic, immunological features of renal involvement in pSS were systematically analyzed. Possible factors related to renal involvement were identified using multivariate logistic regression analyses. Results: One hundred and ninety‐two pSS patients (88.48%) with renal involvement were women with mean age of nearly 58 years and mean disease duration of above 4 years. Clinical manifestation, serologic and immunological features and renal biopsy class of the pSS patients with renal involvement were presented. By multivariate analyses, xerophthalmia, histological positivity for lower salivary gland biopsy (LSGB), anti‐SSA/Ro52‐positive, reduced complement 3 (C3) levels, hypoalbuminemia and anemia retained significant association with renal involvement in pSS (all P  < 0.05). Conclusion: In addition to LSGB pattern, anti‐SSA/Ro52‐positivity, reduced C3 levels, hypoalbuminemia and anemia, also indicate significant association with renal involvement in pSS. Therefore, early vigilance is required for patients with these clinical manifestations.